The Incidence and Risk Factors for Adverse Drug Reactions Related to Tanreqing Injection: A Large Population-Based Study in China - Li, Xiao-Xiao; Zhuo, Lin; Zhang, Yan; Yang, Yi-Heng; Zhang, Hong; Zhan, Si-Yan; Zhai, Suo-Di (Frontiers in Pharmacology, 2020)
BACKGROUND: Tanreqing injection (TRQ) is a traditional Chinese medicine commonly used in China to treat pulmonary diseases presenting as Phlegm-Heat syndrome. Robust data on the safety of TRQ from real-world observational cohorts are currently lacking. OBJECTIVE: To evaluate as the incidence, type and predictors of adverse events (AEs) and adverse drug reactions (ADRs) of TRQ in clinical practice in China. METHODS: We conducted a population-based cohort, multicentre study to evaluate the incidence, manifestation, outcomes and risk factors of AEs and ADRs following TRQ use in China. Between April 2014 and May 2015 a total of 30,322 consecutive inpatients/ emergency attendance patients from 90 hospitals across China administrated TRQ were followed-up for 7 days. Odds ratios (ORs_ with 95% confidence intervals (CIs) were estimated using logistic regression to identify predictors of ADRs. RESULTS: The incidence of AEs and ADRs was 1.4% and 0.3%, respectively. Skin and subcutaneous tissue disorders were the most common ADRs. All ADRs were mild or moderate in severity, except for one serious case of anaphylactic reaction. The majority of ADRs (72.8%) occurred in the first 2 hours after TRQ administration. Two-thirds of patients (66.1%) in the study were prescribed TRQ off-label, including infants aged ≤24 months. A history of food allergy (OR 4.50, 95% CI: 1.35–15.00), drug allergy (OR 2.77, 95% CI: 1.56–4.94), and fast infusion speed (off-label use) (OR 2.10, 95% CI: 1.27– 3.50) were associated with an increased risk of ADRs. CONCLUSION: TRQ is well tolerated in the general population, yet off-label use is prevalent. Efforts are required to educate prescribers to adhere to the drug label in order to minimize potential patient harm.